T Cells as an Emerging Target for Chronic Pain Therapy - Laumet, Geoffroy; Ma, Jiacheng; Robison, Alfred J.; Kumari, Susmita; Heijnen, Cobi J.; Kavelaars, Annemieke (Frontiers in Molecular Neuroscience, 2019)
The immune system is critically involved in the development and maintenance of chronic pain. However, T cells, one of the main regulators of the immune response, have only recently become a focus of investigations on chronic pain pathophysiology. Emerging clinical data suggest that patients with chronic pain have a different phenotypic profile of circulating T cells compared to controls. At the preclinical level, findings on the function of T cells are mixed and differ between nerve injury, chemotherapy, and inflammatory models of persistent pain. Depending on the type of injury, the subset of T cells and the sex of the animal, T cells may contribute to the onset and/or the resolution of pain, underlining T cells as a major player in the transition from acute to chronic pain. Specific T cell subsets release mediators such as cytokines and endogenous opioid peptides that can promote, suppress, or even resolve pain. Inhibiting the pain-promoting functions of T cells and/or enhancing the beneficial effects of pro-resolution T cells may offer new disease-modifying strategies for the treatment of chronic pain, a critical need in view of the current opioid crisis.